Stages of Behavior Change for Physical Activity in Airport Staff: a quasi-experimental study - Mahmoudi, Khalil; Taghipoor, Ali; Tehrani, Hadi; Zomorodi Niat, Hadi; Vahedian-Shahroodi, Mohammad (Investigación y Educación en Enfermería, 2020)
Objective. This work sought to determine the effect of an educational intervention based on the stages of change in promoting physical activity in employees in the Mashhad airport in Iran. Methods. This was a quasi-experimental study conducted with the participation of 60 volunteers (30 in the intervention group and 30 in the control group) who were in the stages of contemplating or preparing for change in physical activity. The intervention consisted in educational activities provided during home visits, telephone calls, group training sessions, and delivery of printed material. To gather the information, the study used five questions on the stage in which they were for behavioral change in physical activity, according to the Theoretical Model by Marcus et al., (1. pre-contemplation, 2. contemplation, 3. preparation, 4. action, and 5. maintenance), and the International Questionnaire on Physical Activity. Changes in the stages were evaluated during three moments: upon entering the study, at the end of the intervention (8th month), and two months after the second evaluation (10th month). Results. During the 10th month evaluation, it was noted that 26.7% of the subjects from the intervention group versus 3.3% from the control group improved their physical activity and were in the action stage (p<0.01). Conclusion. Theeducational intervention based on stages of change is effective in promoting physical activity in the participants and may be used in educational programs that seek to improve physical activity in the employees studied. How to cite this article: Mahmoudi K, Taghipoor A, Tehrani H, Zomorodi Niat H, Vahedian-Shahroodi M. Stages of Behavior Change for Physical Activity in Airport Staff: a quasi-experimental study. Invest. Educ. Enferm. 2020; 38(1):e02